(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
English language is full of interesting and endless meaningful phrases and idioms which makes the speech and writing more fascinating. The role of using phrases and idioms in English languages has a great impact on high score especially on both writing and speaking. This article is devoted to this issue and highlights the importance of idioms, phrases, phrasal sentences and some rules that required in complex sentences in order to achieve colourful and unrepeatable score on language competence. Even thought this issue can be seen to be a bit challenging, but it is worth analysing and searching more data regarding this theme.